Weak gravitational lensing by voids - Amendola, Luca; Frieman, Joshua A.; Waga, Ioav (Arxiv, 2008)
We consider the prospects for detecting weak gravitational lensing by underdensities (voids) in the large-scale matter distribution. We derive the basic expressions for magnification and distortion by spherical voids. Clustering of the background sources and cosmic variance are the main factors which limit in principle the detection of lensing by voids. We conclude that only voids with radii larger than $\sim 100$ \hm have lensing signal to noise larger than unity.